Analisis Peran Polri Saat Negara dalam Keadaan Darurat Militer - M. Zendi Kharisma; Prastopo Prastopo; A. Makbul (Wajah Hukum, 2025)
Polri's main responsibilities are to uphold public security and order, enforce the law, and provide protection and services to the public. During martial law and wartime, Polri functions as a State Defense Resource to carry out state defense operations. This study seeks to explain the function of Polri during Martial Law, drawing lessons from the implementation of Martial Law in Aceh. The Polri has a dual role, particularly a special function in assisting military operations, with deployment through mobilization to augment and improve the strength and capabilities of the TNI. Polri's role is to enforce the law and maintain security in areas under martial law, by ensuring compliance with applicable laws and regulations. This research utilizes a data collection strategy that involves information gathered through interviews and document analysis from various relevant sources. The conclusion that can be drawn is that it is imperative to consider the future role of Polri in the context of martial law and states of emergency, with regard to the regulation of duties, powers, and responsibilities, as well as the strategies employed by Polri. Effective law enforcement can provide a deterrent effect, suppress insurgents, and simultaneously gain legitimacy and public support. This research aims to enable Polri to participate in the implementation of Military Operations in the future.